2021
DOI: 10.1038/s41467-021-22133-z
|View full text |Cite|
|
Sign up to set email alerts
|

Direct observation of excitonic instability in Ta2NiSe5

Abstract: Coulomb attraction between electrons and holes in a narrow-gap semiconductor or a semimetal is predicted to lead to an elusive phase of matter dubbed excitonic insulator. However, direct observation of such electronic instability remains extremely rare. Here, we report the observation of incipient divergence in the static excitonic susceptibility of the candidate material Ta2NiSe5 using Raman spectroscopy. Critical fluctuations of the excitonic order parameter give rise to quasi-elastic scattering of B2g symme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 56 publications
(66 reference statements)
4
39
0
Order By: Relevance
“…The reduced dimensionality of TMCs results in weak screening of the Coulomb interaction and consequently large exciton binding energies, which could lead to condensation at noncryogenic temperatures. Among this family of materials, particular attention has been devoted to Ta 2 NiSe 5 following hints of the potential existence of an EI phase below 328 K (8)(9)(10)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). These works have provided insights into the properties in Ta 2 NiSe 5 , for instance, by using equilibrium (8,12) and time-resolved (9,17,18,21,23) angle-resolved photoemission spectroscopy (ARPES), by analyzing the effect of physical and chemical pressure (14,22), by doping (16), and by detecting anomalies in charge transport (14), optical signatures (24,25), and phonon properties (10,15,19,20,22,26) as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced dimensionality of TMCs results in weak screening of the Coulomb interaction and consequently large exciton binding energies, which could lead to condensation at noncryogenic temperatures. Among this family of materials, particular attention has been devoted to Ta 2 NiSe 5 following hints of the potential existence of an EI phase below 328 K (8)(9)(10)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). These works have provided insights into the properties in Ta 2 NiSe 5 , for instance, by using equilibrium (8,12) and time-resolved (9,17,18,21,23) angle-resolved photoemission spectroscopy (ARPES), by analyzing the effect of physical and chemical pressure (14,22), by doping (16), and by detecting anomalies in charge transport (14), optical signatures (24,25), and phonon properties (10,15,19,20,22,26) as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…While we qualitatively explain the observed spectral behaviours using a single phonon mode, further experiments have indicated multiple phonons involved in this transition: the diffuse scattering and inelastic x-ray scattering results point to extensive transverse acoustic phonon softening 38 ; Raman scattering also suggest strong involvement of optical phonons [20][21][22] . Distinct from the acoustic-phonon-driven structural transition in 3D perovskite PrAlO3 45 , the strong fluctuations in Ta2NiSe5 seem to suggest additional contributions from the lower system dimension and optical phonons.…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In the pursuit of a potential room-temperature Bose-Einstein condensate, recent studies revealed evidence for exciton formation, strong lattice instability and electron-phonon coupling in quasi-1D ternary chalcogenide Ta2NiSe5 [19][20][21][22] . Upon warming, a q = 0 monoclinic-to-orthorhombic structural transition happens at Ts~329K, above which a semi-metallic electronic structure is supposedly restored and protected by the mirror symmetry of Ta chains about the Ni chain 23 .…”
Section: Mainmentioning
confidence: 99%
See 2 more Smart Citations